2023
DOI: 10.1021/acs.inorgchem.2c04368
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Optical Properties of Large-Sized NaVO2(IO3)2(H2O) Crystals for Second-Harmonic Generation Applications

Abstract: Large-sized crystals of the quaternary iodate NaVO2(IO3)2(H2O) (NVIO) with centimeter-scale dimensions (23 mm × 18 mm × 6 mm as a representative) have been successfully grown by the top-seeded hydrothermal method. Linear optical properties have been measured, including the optical transmission spectrum and refractive index. The NVIO crystal possesses an optical window with high transmittance (above 80%) over the range of 500–1410 nm and exhibits strong optical anisotropy with large birefringence Δn (nz – nx )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Exploring new material systems is of great importance, because it contributes to expand the chemical space and discovery novel materials with unique properties and potential applications. By investigating new inorganic compound systems, researchers can uncover unprecedented structural motifs, understand the relationships between structures and properties, and potentially develop advanced materials for various technological applications. Selenites have garnered the attention of scientists due to their unique physical and chemical properties. They possess stereochemically active lone-electron pairs, making them promising candidates of nonlinear optical (NLO) and birefringent materials . Over the past few decades, research on selenite compounds has identified over a thousand different chemical entities.…”
mentioning
confidence: 99%
“…Exploring new material systems is of great importance, because it contributes to expand the chemical space and discovery novel materials with unique properties and potential applications. By investigating new inorganic compound systems, researchers can uncover unprecedented structural motifs, understand the relationships between structures and properties, and potentially develop advanced materials for various technological applications. Selenites have garnered the attention of scientists due to their unique physical and chemical properties. They possess stereochemically active lone-electron pairs, making them promising candidates of nonlinear optical (NLO) and birefringent materials . Over the past few decades, research on selenite compounds has identified over a thousand different chemical entities.…”
mentioning
confidence: 99%
“…13–17 To be commercially available, UV NLO materials need to simultaneously meet the following conditions: (a) a large second harmonic generation (SHG) response, (b) a wide band gap, (c) a high laser-induced damage threshold (LIDT), (d) high thermal stability and excellent environmental stability, and (e) sufficient birefringence to satisfy phase matching. 18–24 Due to the contradiction between the above conditions, it is very difficult to synthesize UV NLO materials with balanced properties. Therefore, how to design UV NLO materials with balanced performance is a very urgent task.…”
Section: Introductionmentioning
confidence: 99%
“…17,[31][32][33][34][35] It should be mentioned that a crystalline water molecule is also a remarkable regulatory factor of BBU alignment due to its intrinsic space occupancy and character that easily forms hydrogen bonds. Many NCS crystals containing water molecules have been developed as potential NLO materials, such as NaVO 2 (IO 3 ) 2 (H 2 O), 36 BaGe(IO 3 ) 6 •H 2 O, 33 and [C(NH 2 ) 3 ] 6 (PO 4 ) 2 •3H 2 O. 37 Whether the water molecule can be applied to adjust the orientation of Λ-shaped BBUs to assemble the NCS structure based on CS crystals still remains a question.…”
Section: Introductionmentioning
confidence: 99%